Singular Electromagnetics: From Phase Singularities to Optical Skyrmions and Beyond (Adv. Phys. Res. 5/2025) - Yang, Jie; Jiang, Juanna; Wang, Jiafu; Zheng, Xuezhi (Advanced Physics Research, 2025)
Singular Electromagnetics A vortex of twisted light beams serves as a streamline to organize and present the primary research objectives of singular electromagnetics/singular optics. As reviewed by Jiafu Wang, Xuezhi Zheng and co‐workers in article number 2400083, these objectives include phase singularities in complex scalar fields, polarization singularities in complex vector fields, and 3D topological defects (specifically, four types are presented: optical skyrmions, hopfions, knots, and Möbius strips). These research objectives are well‐recognized within the communities of electromagnetics, optics, photonics, metamaterials, and plasmonics, as well as acoustics, while also capturing the attention of a broader audience from other research fields or even non‐research readers.